2022
DOI: 10.15446/agron.colomb.v40n2.101854
|View full text |Cite
|
Sign up to set email alerts
|

Altitude as a determinant of fruit quality with emphasis on the Andean tropics of Colombia. A review.

Abstract: Due to global warming, the highlands of the tropics have become more important for planting fruit trees. The climate at high altitudes is mainly characterized by decreased temperatures and increased solar radiation. A systematic literature review using four bibliographic databases revealed 22 studies that determined fruit quality at two altitudes. With increasing altitude, duration of fruit development was prolonged, and, in most cases, higher fresh weights and sizes were found; however, fruit firmness decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 85 publications
1
18
0
Order By: Relevance
“…The total phenol content was higher in Citrus limon , Citrus aurantifolia , and Citrus maxima collected from Lamjung. This study was supported by previous studies [ 32 34 ]. The increase in altitude may cause a decrease in temperature and ascribe as a response of plants to radiation which causes amplified biosynthesis of UV-absorbing and enhanced UV-B antioxidant phenolics in plants.…”
Section: Discussionsupporting
confidence: 92%
“…The total phenol content was higher in Citrus limon , Citrus aurantifolia , and Citrus maxima collected from Lamjung. This study was supported by previous studies [ 32 34 ]. The increase in altitude may cause a decrease in temperature and ascribe as a response of plants to radiation which causes amplified biosynthesis of UV-absorbing and enhanced UV-B antioxidant phenolics in plants.…”
Section: Discussionsupporting
confidence: 92%
“…According to a study by Dinis et al [ 28 ], the morphological and phenological differences among different ecotypes of the Portuguese chestnut (Judia cultivar) are related to the small genetic variations and phenotypic adaptations to different climatic conditions. Fischer et al [ 29 ] pointed out that an increases in altitude cause an increase in antioxidant content in various fruit species, a reaction to increasing UV light. It is known that various factors, such as the climatic conditions, cultivars, geographical area, soil nutrients and water availability may affect the bioactive composition of chestnut fruits.…”
Section: Resultsmentioning
confidence: 99%
“…The avocado was cultivated under both traditional and organic production systems. This was to confirm whether the biostimulant improves fruit production without negatively affecting postharvest performance since it has been reported that pre-harvest factors and practices can impact the post-harvest quality of the fruits [20,21].…”
Section: Introductionmentioning
confidence: 76%